(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: Little is known about primary care professionals’ concerns about risks to patient safety. AIM: To identify threats to patient safety in the primary care office from the perspective of physicians and nurses. DESIGN: Cross-sectional survey; participants were asked to name and rank threats to safety they personally were most concerned about. SETTING: Physicians and nurses working in primary care offices in Switzerland. METHODS: Verbatim reports were analysed under an inductive content-analysis framework. Coded threats were quantitatively analysed in terms of frequency and prioritisation. Differences between physicians and nurses were analysed. RESULTS: Of 1260 invited individuals, 630 responded to the survey and 391 (31%) described 936 threats to patient safety. The coding system included 29 categories organised in 5 themes. Agreement of coders was good (kappa = 0.87, CI = 0.86–0.87). Safety of medication (8.8%), triage by nurses (7.2%) and drug interactions (6.8%) were the threats cited most frequently. Errors in diagnosis (OR = 0.21, CI 0.09–0.47, p <0.001), drug interactions (OR = 0.10, CI 0.04–0.25, p <0.001) and compliance of patients (OR = 0.28, CI 0.08–0.96, p = 0.044) were more likely to be cited by physicians. X-rays (OR = 3.34, CI 1.04–10.71, p = 0.043), confusion of patients or records (OR = 3.28, CI 1.55–6.94, p = 0.002), hygiene (OR = 3.21, CI1.12–9.19, p = 0.030), safety of office rooms (OR = 6.70, CI 1.46–30.73, p = 0.014), and confidentiality (OR = 7.38, CI 1.63–33.50, p = 0.010) were more likely to be described by nurses. CONCLUSION: Physicians and nurses are concerned about diverse threats to patient safety in primary care. Involving both groups in detection and analysis of risks in medical offices seems a valuable strategy to improve collaboration and safety.